2010
DOI: 10.1111/j.1365-2044.2010.06294.x
|View full text |Cite|
|
Sign up to set email alerts
|

A comparison between the GlideScope® Video Laryngoscope and direct laryngoscope in paediatric patients with difficult airways – a pilot study

Abstract: Summary The GlideScope® Video Laryngoscope may improve the view seen at laryngoscopy in adults who have a difficult airway. Manikin studies and case reports suggest it may also be useful in children, although prospective studies are limited in number. We hypothesised that the paediatric GlideScope will result in an improved view seen at laryngoscopy in children with a known difficult airway, compared to direct laryngoscopy. Eighteen children with a history of difficult or failed intubation were prospectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 18 publications
(23 reference statements)
1
33
0
Order By: Relevance
“…Also in a study including children who are known to have a difficult airway, the use of the GlideScope videolaryngoscope, with and without laryngeal pressure, significantly improves the Cormack and Lehane grade at laryngoscopy. [11] In this study, the tracheal intubation time was significantly shorter with the Glide Scope ® video laryngoscope (GVL) than with the Macintosh laryngoscope and the LMA CTrach™. In our study significantly more maneuvers (Laryngeal mask manipulation) were applied for the satisfactory ventilation and viewing of the glottis with the LMA CTrach™ (30%) versus 0% for GVL and DL ( P < 0.05) and this explain the longer time for intubation with LMA CTrach™ and improved overall success rate.…”
Section: Discussionmentioning
confidence: 75%
“…Also in a study including children who are known to have a difficult airway, the use of the GlideScope videolaryngoscope, with and without laryngeal pressure, significantly improves the Cormack and Lehane grade at laryngoscopy. [11] In this study, the tracheal intubation time was significantly shorter with the Glide Scope ® video laryngoscope (GVL) than with the Macintosh laryngoscope and the LMA CTrach™. In our study significantly more maneuvers (Laryngeal mask manipulation) were applied for the satisfactory ventilation and viewing of the glottis with the LMA CTrach™ (30%) versus 0% for GVL and DL ( P < 0.05) and this explain the longer time for intubation with LMA CTrach™ and improved overall success rate.…”
Section: Discussionmentioning
confidence: 75%
“…We agree with the authors' view that the BURP manoeuvre (backward, upward and right-sided pressure on the larynx) provides better glottic exposure using the paediatric GlideScope. Overall, the paediatric GlideScope, with or without the BURP manoeuvre, provided a better glottic view than the Macintosh laryngoscope in the same study [1]. However, in 6 of their 18 children, the paediatric GlideScope without the BURP manoeuvre provided a view of the glottis that was equal to or worse than that by the Macintosh laryngoscope without the BURP manoeuvre (Cormack-Lehane grade 3 and 4).…”
Section: T Mccormickmentioning
confidence: 72%
“…We read with interest the article by Karsli et al [1], which demonstrated the usefulness of the paediatric GlideScope Ò video laryngoscope (Verathon Medical Inc., Bothell, WA, USA) in children with a difficult airway, relative to conventional direct laryngoscopy using the Macintosh blade. We agree with the authors' view that the BURP manoeuvre (backward, upward and right-sided pressure on the larynx) provides better glottic exposure using the paediatric GlideScope.…”
Section: T Mccormickmentioning
confidence: 99%
See 2 more Smart Citations